The Role of Carrier Media and Types of Indigenous MVA Isolates on Soil Quality in Corn Plants in the Dry Land of West Nusa Tenggara - Sukmawati Sukmawati; I Made Adnyana; Dewa Ngurah Supraptha; Riski Busaifi (Jurnal Penelitian Pendidikan IPA, 2023)
Corn plants have many benefits and are needed by the government as a national food reserve. West Nusa Tenggara (NTB) maize production fluctuated. If managed optimally, dry land agriculture in NTB can provide benefits for increasing agricultural production, especially corn production. The sustainability of dry land farming systems must be continuously improved even with various farming strategies with the main objective of improving soil fertility and overcoming drought stress constraints. One of the efforts to increase the productivity of NTB's dry land is the use of arbuscular vesicular mycorrhizal biofertilizers which are an alternative to improve the quality of soil and plants. Arbuscular vesicular mycorrhiza will colonize and infect roots maximally if using a carrier media that is compatible with MVA inoculant. Appropriate MVA carrier media will provide optimal environmental conditions for host plant growth. The aim of the research was to determine the role of Indigenous MVA and carrier media on soil quality in dryland maize. The research was carried out on corn plants using different carrier media and native MVA types. The study was designed as a factorial study using a completely randomized design (CRD) with 2 factors, namely the type of indigenous MVA isolates with 3 treatment levels and the Carrier Media Type factor with 4 treatment levels. There were 12 treatment combinations that were repeated 3 times so that 36 treatment combinations were obtained which were carried out at the Green House of the Faculty of Agriculture, Nahdhatul Wathan University, Mataram from December 2020 to February 2021. The results showed that the MVA type factor, the MVA isolate had a significantly different effect for all observation parameters, namely soil water content, soil pH, soil total N content and soil available P content, the best isolate was Glomus sp. The carrier media factor gives the result that the type of carrier media has a significant effect on the parameters of observing soil water content, soil total N content and soil pH with the best carrier media being rice husk charcoal biochart